Antibacterial activity of the lichens Usnea Florida and Flavoparmelia caperata (Parmeliaceae). Issue 23 (1st December 2020) - Dieu, Amandine; Mambu, Lengo; Champavier, Yves; Chaleix, Vincent; Sol, Vincent; Gloaguen, Vincent; Millot, Marion
Abstract: Acetone extracts of the two common epiphytes lichens Usnea florida and Flavoparmelia caperata have been evaluated for their antimicrobial activities against Staphylococcus aureus, Candida albicans and Aspergillus brasiliensis . The dibenzofuran derivative (+)-usnic acid (1 ) was the main metabolite in these two species. Thamnolic (5 ), evernic (6 ), physodic (7 ) and 3-hydroxyphysodic acids (8 ) were isolated from U. florida, as well as 5, 7-dihydroxy-6-methylphtalide (2 ) which was newly identified in this Genus . Protocetraric (3 ) and caperatic acids (4 ) and ergosterol peroxide (9 ) are usually biosynthezised by F. caperata . Antibacterial activity was determined for the four main compounds against Staphylococcus aureus using bioautography and broth dilution method. Minimal inhibitory concentrations of usnic acid, caperatic acid and protocetraric acid were comprised between 7.25 and 12.5 µg/mL. Graphical Abstract: